RASIO KEUANGAN SEBAGAI PREDIKTOR LABA DAN ARUS KAS DI MASA YANG AKAN DATANG - Yustina Sandiyani, Titik Aryati (Media Riset Akuntansi, Auditing & Informasi, 2001)
The objective of the research is to test the relationship between financial information variables with their ability to predict the changes of earning and cash flows for one year. The financial information used in the research are earnings, cash flows, accounts receivable, inventory, selling and administrative expense, and gross profit to sales ratio. The financial information from financial reports were taken from Jakarta Stock Exchange, which has published during 1992 to 1997 by manufacturing firms. The first hypothesis is the financial information will predict the eaming’changes, and the second is that they will predict the cash flows changes for one year.The test was using multiple regression with a = 5%. The statistical result show the adjusted R square for first hypothesis was 90.3% and for the second was 68.3%. They also show that financial information is usefull in predicting earnings and cash flows canges. For first hypothesis, all financial information are significant except inventory, and for second hypothesis cash flows, account receivables, and selling and administration expense are significant.